Fauna and taxonomy of Diamesinae (Diptera, Chironomidae) from the Caucasus, with a morphological description and DNA barcoding of new taxa and a discussion of diagnostic problems for Diamesa Meigen and Pseudodiamesa Goetghebuer - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2023)
As a result of the revision of adult males as well as available literature data, 26 species of the subfamily Diamesinae are registered for the Caucasus, belonging to 5 genera. Four species are recorded for the first time for this region, one species, D. elbrusica sp. nov., and one subspecies, D. sakartvella gidanica subsp. nov., are new to science and are described. Six species are classified as endemics of the Caucasus. Distribution of other species of Caucasian Diamesinae is discussed. DNA barcodes of 102 specimens and 20 species of four genera, Boreoheptagyia Brundin, Diamesa Meigen, Pseudodiamesa Goetghebuer and Syndiamesa Kieffer were obtained in this study. Of these, 12 species were deposed in the GenBank and BOLD systems for the first time. We have established that D. cinerella group includes D. kasymovi and probably D. lavillei whereas D. zernyi group includes D. vaillanti and D. valentinae. Highly supported phylogeny and results of species delimitation suggest the description of D. elbrusica sp. nov. and D. sakartvella gidanica subsp. nov. Ps. aff. branickii and Ps. aff. nivosa are new species based on DNA barcoding. The results of species delimitation show that genus Pseudodiamesa includes 10 (ASAP, GMYC), 14 (mPTP) or 21 (BOLD) distinct molecular taxonomic units (mOTUs) among which only Ps. stackelbergi have an undoubted species status that requires a large revision using both morphological and molecular approaches.